Formulation of Full Instant Functional Drinking Making With Coffee Addition - Pranowo, Dodyk; Perdan, Claudia i Gadizza; Budiarto, Alim (El-Hayah : Jurnal Biologi, 2019)
Galangal (Alpinia officinarum) is a type of rhizome plant such as ginger. Utilization of galangal which is still well known by the public is a spice in cooking and as a traditional herbal medicine that has not yet attracted people's interest. Further processing needs to be done to attract the public so that they can benefit from galangal. The study was designed using a Randomized Block Design (RCBD) using 2 factors. Comparison of  coffee and  galangal are  9: 1, 7: 3, 5: 5, and factor 2 for 50 grams of sugar, 100 grams, and 150 grams. The research results obtained by the panelists the most important formulation is the ratio of galangal and coffee 7: 3 with the approval of 150 grams of coconut sugar. The results of the antioxidant activity test obtained data about instant galangal functional drinks having antioxidant content of IC50 8.10 mg/ml have not been approved as functional drinks. The results of the caffeine content test showed that instant galangal functional drinks had caffeine levels of 2.63 ± 0.04%